Efforts to Increase Students' Understanding of Islamic Religious Education Learning Using Islamic Comic Media: Study in TK Al-Azizi - Nurhayati; Afrizal, Rahmi (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students’ understanding of Islamic Religious Education (PAI) by utilizing Islamic comic media at Al-Azizi Kindergarten. The research employed classroom action research (CAR) over two cycles. Data were collected through pre-tests, post-tests, classroom observations, and student interviews, and analyzed using both quantitative and qualitative descriptive methods. Initially, only 45% of students met the minimum mastery level in understanding PAI concepts. After the first intervention cycle using Islamic comics, the mastery percentage increased to 70%. Refinements led to a further increase in the second cycle, with 88% of students achieving mastery. Observations and interviews showed higher student engagement, increased questioning, and better use of religious vocabulary. The study concludes that Islamic comic media significantly enhances understanding of Islamic religious concepts among kindergarten students by contextualizing learning, stimulating interest, and providing scaffolding for young learners.